Composite event‐triggered H∞ control for nonlinear switched singular systems with a mode‐dependent triggering strategy - Yang, Anqing; Zhao, Zhenli; Shi, Hongpeng; Ma, Shuping (International journal of robust and nonlinear control, 2023)
Summary This paper considers the event‐triggered H∞ control problem of nonlinear switched singular systems (NSSSs) with incremental quadratic constraints (IQCs) via a mode‐dependent hybrid triggering strategy. First, impulsive control is introduced to reduce the effect of impulse caused by switching, and the closed‐loop system is modeled as an impulsive NSSS. Then, a novel mode‐dependent hybrid event‐triggering strategy (ETS) consisting of disturbance‐influenced ETS and Lyapunov‐function‐dependent ETS is constructed to avoid Zeno behavior and asynchronous phenomena. Based on this ETS and admissible edge‐dependent average dwell time (AED‐ADT) method, some new sufficient conditions in terms of linear matrix inequalities (LMIs) are derived to ensure that the closed‐loop system is regular, impulse‐free, has a unique solution, and is globally uniformly asymptotically stable (GUAS) with a weighted H∞ performance. Further, Zeno behavior is excluded by calculating the minimum lower bound of inter‐event time. Finally, a numerical example and a practical application are proposed to demonstrate the validity of the results.